Earned Value Management System in Indonesian Construction Projects - Priyo, Manidyo (International Journal of Integrated Engineering, 2021)
Earned Value Management (EVM) is a methodology combining scope, schedule, and resource measurements to assess project performance and progress. It involves integrating the three critical elements of the project covering schedule, work scope, and cost. Various benefits are associated with the use of EVM in project management. This research aims to analyze four units of building construction projects using the EVM method consisting of an analysis of project performance, estimation of cost, and time for project completion, and planning estimation analysis against project completion. The results revealed that from the aspect of time, three buildings were completed ahead of schedule, and another one was behind schedule. In terms of cost, three buildings cost lower than the estimated budget, while one other building was higher.